Soundtracks of Asian America : Navigating Race through Musical Performance - Wang, Grace, 1972- (Book collections on Project MUSE., 2015)
Soundtracks of Asian America explores how Asian Americans use music to construct narratives of self, race, class, and belonging in national and transnational spaces by considering the experiences of Asians and Asian Americans in Western classical music, U.S. popular music, and Mandopop (Mandarin-language popular music).